Organochlorine pesticide residues in different fishes and shell fishes collected from the flood plains of Sonargaon upazila, Bangladesh (Bangladesh Journal of Zoology, 2019)
The present study was carried out to assess the concentrations of organochlorine pesticide residues (DDTs; DDE, DDD, 2,4´-DDT and 4,4´-DDT) in natural fishes and prawn species during rainy-season (June-September, 2014) from flood plains of Sonargaon upazila, Bangladesh. The samples were extracted by Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) method and the extracts were cleaned-up by using H2SO4. Analysis of the samples for DDTs residues were carried out by using Gas Chromatograph with Electron Capture Detector (GC-ECD). Controlled fish sample (Cultured Rui fish) was used for the recovery experiments. Percent (%) recovery was found to be in the range of 70%- 113%. The total DDTs contents of the head of different fish and prawn species ranged from 7.53 ± 0.50 ng/g in Jatpunti (P. sophore) to 39.20 ± 3.76 ng/g in Bele (G. giuris) and of the body from 7.55 ± 0.50 ng/g in Jatpunti (P. sophore) to 41.93 ± 3.63 ng/g in Chewa (P. elongatus). While the total DDTs of the total body of seven fish and two prawn species ranged from 4.56 ng/g in Gurachingri (unidentified) to 37.15 ng/g in Chewa (P. elongatus). In the present study, 66.66% samples having value of (DDE + DDD)/DDT, lower than 0.5 ratios indicated the presence of new DDT inputs in the environments of Sonargaon area. The concentrations of total DDTs in all the samples were within the permissible MRL level i.e. for human consumption recommended by FAO-IAEA-WHO. As DDT is a long persistent and bioaccumulative substance in the environment, intake of significant amount of these toxic elements with our diet is a matter of great health concern.Bangladesh J. Zool. 47(1): 137-148, 2019